2016
DOI: 10.1097/md.0000000000004442
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic duodenum-preserving pancreatic head resection

Abstract: Background:Solid pseudopapillary neoplasms (SPNs) of the pancreas are uncommon neoplasms and are potentially malignant. Complete resection is advised due to rare recurrence and metastasis. Duodenum-preserving pancreatic head resection (DPPHR) is indicated for SPNs located in the pancreatic head and is only performed using the open approach. To the best of our knowledge, there are no reports describing laparoscopic DPPHR (LDPPHR) for SPNs.Methods:Herein, we report a case of 41-year-old female presented with a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Presently, only a few studies have reported LDPPHR based on surgical experience and case reports. In 2016, Zhou et al [ 15 ] reported the first case of LDPPHR for treating a solid pseudopapillary tumor present on the pancreatic head. In 2019, Cao et al [ 16 ] reported 12 patients who underwent LDPPHR for the treatment of benign and low-grade malignant tumors of the pancreatic head, which opened up a minimally invasive way for LDPPHR for treating benign or low-grade malignant tumors of the pancreatic head.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, only a few studies have reported LDPPHR based on surgical experience and case reports. In 2016, Zhou et al [ 15 ] reported the first case of LDPPHR for treating a solid pseudopapillary tumor present on the pancreatic head. In 2019, Cao et al [ 16 ] reported 12 patients who underwent LDPPHR for the treatment of benign and low-grade malignant tumors of the pancreatic head, which opened up a minimally invasive way for LDPPHR for treating benign or low-grade malignant tumors of the pancreatic head.…”
Section: Discussionmentioning
confidence: 99%
“…DPPHR was initially introduced for chronic pancreatitis by Beger [6] and was proven to decrease the long-term endocrine and exocrine dysfunction compared with pancreaticoduodenectomy (PD) [2,3]. However, in terms of laparoscopic DPPHR, our team reported the first case in 2016 [7]; later on, a few studies reported 12-24 cases are complicated with astonishing biliary leakages of 4.5-16.7% without exception [8][9][10]. Moreover, none of them reported the long-term metabolic dysfunction, which was of great importance on deciding whether to perform L-DPPHR or not.…”
Section: Discussionmentioning
confidence: 99%
“…After the removal of the specimen, fluorescent cholangiography was also performed to detect the suspicious injury of the bile duct. Finally, a direct pancreaticogastrostomy or Roux-en-Y end-to-side pancreaticojejunostomy (duct to mucosa) was performed [7]. Two drainage tubes were placed behind the anastomosis.…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, intraoperative blood loss less than OPD was 120 mL and no transfusion was found reducing the risks of PPC. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%